Applications of Right Speech in Knowledge Management and Organizational Learning - Mishra, Kalpana (Bodhi: An Interdisciplinary Journal, 2019)
The focus of this research is more on the applications of Right Speech (RS) in Knowledge Management (KM) and Organizational Learning (OL) in the context of Nepal. The primary motivation of the researcher is to see whether people at the managerial level do use right speech in relation to KM and OL. We would agree the fact that the job of quantifying values into numeric system is not an easy one; therefore, mixed-method has been carried out as a tool so as to interpret the quantitative, qualitative, and the content of Key Informant Interviews (KIIs). The mixed-method is the integration of qualitative and quantitative approaches or methods in a single study or program of inquiry, and this is what the researcher has done here in the Nepalese organizations that deal with various sectors such as education, finance, human resource development, profit and non-profit etc.